Pengaruh Penambahan Glukosa terhadap Pertumbuhan Bakteri Escherichia coli pada Media Pemupuk Nutrient Broth (NB) - Hidayati, Nurul; Sukmana, Dhika Juliana; Ariami, Pancawati; Urip, Urip; Fihiruddin, Fihiruddin (Puslitbang Sekawan Institute Nusa Tenggara, 2024)
Infectious diseases are caused by microorganisms, one of them is Escherichia coli. The process of isolation and identification of bacteria requires enrichment media to increase the number of bacteria. Media Brain Infusion Broth (BHIB) media, the growth of Escherichia coli bacteria is better than Nutrient Broth (NB). Demahui's glucose as a normal source of organic carbon for the growth of Escherichia coli bacteria, while in NB media there is no glucose. This study is quoted to obey the effect of the addition of glucose on the NB fertilizer media on the growth of Escherichia coli bacteria. This study is a pre-ecperimental study of the addition of 1 gram of glucose, 2 grams, 3 grams, 4 grams and 5 grams of media Nutrient Broth fertilizer media (NB). Termanhan is observed from the number of colonies that grow on the nutrient media so that the plate (NAP). The sample used was the suspension of the pure isolates of the Escherichia coli ATCC 35218. The calculation of the average number of colonies obtained from each treatment was 79, 90, 144, 126, and 103 colonies with a control of 63 colonies. Based on the statistical test one -way ANOVA P value (0,000) <? (0.05) which means there is an influence of the addition of glucose on the growth of Escherichia coli bacteria Nutrient Broth (NB). The optimal concentration of the addition of glucose is 3 grams in 1 L of NB media.